Alternative method for the identification of critical nodes leading to voltage instability in a power system. Issue 3 (16th April 2018) - Adebayo, Isaiah G.; Jimoh, Adisa A.; Yusuff, Adedayo A.; Sun, Yanxia
Abstract : The introduction of new operation enhancement technologies plus increasing application of power electronics, coupled with the continuous increase in load demand, has increased the risk of power networks to voltage instability and susceptibility to voltage collapse. This frequent occurrence of voltage collapse in modern power system has been a growing concern among power system utilities. This paper proposes alternative techniques for the identification of critical nodes that are liable to voltage instability in a power system. The first method is based on the critical mode corresponding to the smallest eigenvalues, while the second technique is based on the centrality measure to identify the most influential node of the networks. The eigenvector centrality measure is formulated from the response matrices of both the load and generator nodes of the networks. The effectiveness of the suggested approaches is tested using the IEEE 30-bus and the Southern Indian 10-bus power networks. The results are compared with the techniques based on the traditional power flow. The whole procedure of the results involved in the identification of critical nodes through the proposed methods is totally non-iterative and thereby saves time and requires less computational burden.